2020
DOI: 10.3390/bios10120213
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanowire Field-Effect Transistor as Biosensing Platforms for Post-Translational Modification

Abstract: Protein tyrosine sulfation (PTS), a vital post-translational modification, facilitates protein–protein interactions and regulates many physiological and pathological responses. Monitoring PTS has been difficult owing to the instability of sulfated proteins and the lack of a suitable method for detecting the protein sulfate ester. In this study, we combined an in situ PTS system with a high-sensitivity polysilicon nanowire field-effect transistor (pSNWFET)-based sensor to directly monitor PTS formation. A pepti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The inset figure represents the change in threshold voltage following each surface modification step. This result is consistent with our previous studies [ 19 , 35 ], which determine the surface modification process by measuring the electrical properties of pSiNWFET.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The inset figure represents the change in threshold voltage following each surface modification step. This result is consistent with our previous studies [ 19 , 35 ], which determine the surface modification process by measuring the electrical properties of pSiNWFET.…”
Section: Resultssupporting
confidence: 93%
“…In addition, the well-developed silicon industry is beneficial to the study of SiNWFET. Many studies have demonstrated the potential of SiNWFET for biosensing applications, including detection of nucleic acids [ 17 ], antibodies and antigens [ 18 ], and protein–protein interactions [ 19 ]. These findings revealed the benefits of SiNWFET, including ultrahigh-sensitivity, real-time, and label-free detection, making it a great potential candidate in biosensor development [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the most recent research work for the identification of SARS-CoV-2 was carried out utilizing a FET-based biosensor decorated with ultra-selective antibodies to capture viral spike proteins. It could recognize as low as 100 fg/mL of the analyte in clinical transport medium [ 157 ]. A portable immunosensor was developed for sensing HIV-1.…”
Section: Surface Modification and Functionalization Of Chem/biofetsmentioning
confidence: 99%
“…The sensitivity of NWFET sensors can be increased by using small silicon nanowires, which increase the ratio of surface area to volume, thereby increasing sensitivity to the external environment. Numerous studies have fabricated nanoscale materials such as nanowires [ 4 , 5 , 6 ], nanotubes [ 7 , 8 ], and nanobelts [ 9 , 10 ] and applied them to biomedical sensors to increase their sensitivity.…”
Section: Introductionmentioning
confidence: 99%